2012
DOI: 10.1111/j.1469-8137.2012.04278.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant genetic and phenotypic changes arising from clonal growth of a single spore of an arbuscular mycorrhizal fungus over multiple generations

Abstract: Summary Arbuscular mycorrhizal fungi (AMF) are highly successful plant symbionts. They reproduce clonally producing multinucleate spores. It has been suggested that some AMF harbor genetically different nuclei. However, recent advances in sequencing the Glomus irregulare genome have indicated very low within‐fungus polymorphism. We tested the null hypothesis that, with no genetic differences among nuclei, no significant genetic or phenotypic variation would occur among clonal single spore lines generated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 32 publications
8
69
2
2
Order By: Relevance
“…Another study failed to find evidence for heterokaryosis, however, and the authors suggested that the genetic variation that they observed potentially could be due to polyploidy, although no studies of ploidy were conducted (14). A recent study of Rhizophagus irregularis (but not isolate DAOM-197198) provided further evidence in favor of heterokaryosis (15), so this remains an open question. Another hypothesis, specific for multicopy ribosomal DNA, is that variation among copies could exist within nuclei of a homokaryotic AM fungus and this is supported by some studies (14,16).…”
Section: Significancementioning
confidence: 99%
“…Another study failed to find evidence for heterokaryosis, however, and the authors suggested that the genetic variation that they observed potentially could be due to polyploidy, although no studies of ploidy were conducted (14). A recent study of Rhizophagus irregularis (but not isolate DAOM-197198) provided further evidence in favor of heterokaryosis (15), so this remains an open question. Another hypothesis, specific for multicopy ribosomal DNA, is that variation among copies could exist within nuclei of a homokaryotic AM fungus and this is supported by some studies (14,16).…”
Section: Significancementioning
confidence: 99%
“…Rapid genotypic and phenotypic change in mycorrhizal fungi C Angelard et al frequency (Angelard et al, 2010;Ehinger et al, 2012).…”
Section: Molecular Methodsmentioning
confidence: 99%
“…We carried out quantitative analyses on the frequency of alleles at the Bg112 locus in the AMF lines on different hosts as they signify potential changes in relative nucleotype frequency (Angelard et al, 2010;Ehinger et al, 2012). Four alleles of the Bg112 locus co-occur in each AMF line and can be distinguished by length and sequence polymorphism (Angelard et al, 2010).…”
Section: Molecular Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the level of genetic difference among nuclei is still a topic of heated debate [81,82], it is well established that a single AM fungal spore can contain hundreds of nuclei [83 -85]. From this individual spore, an array of genetically different progeny-displaying different phenotypes-can potentially arise [86]. While the exact mechanism is not well understood, the fungal phenotype is thought to be a reflection of the frequency of different nucleotypes within the individual fungus [87,88].…”
Section: (B) Implications Of Inclusive Fitness For Fungal Symbiontsmentioning
confidence: 99%